2017
DOI: 10.1192/bjp.bp.116.187773
|View full text |Cite
|
Sign up to set email alerts
|

Initial severity of depression and efficacy of cognitive–behavioural therapy: Individual-participant data meta-analysis of pill-placebo-controlled trials

Abstract: The influence of baseline severity has been examined for antidepressant medications but has not been studied properly for cognitive-behavioural therapy (CBT) in comparison with pill placebo.To synthesise evidence regarding the influence of initial severity on efficacy of CBT from all randomised controlled trials (RCTs) in which CBT, in face-to-face individual or group format, was compared with pill-placebo control in adults with major depression.A systematic review and an individual-participant data meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 36 publications
4
41
0
1
Order By: Relevance
“…Unfortunately, only two studies examined combined treatment versus psychotherapy alone among patients with severe depression, so we cannot be certain whether combined treatment is superior for these people. Individual patient data meta‐analyses have suggested that baseline depression severity does not moderate the efficacy of CBT versus antidepressant treatment, or CBT over pill placebo. This supports the notion that combined treatment should be the first option for moderate and probably also severe depression.…”
Section: Discussionmentioning
confidence: 70%
“…Unfortunately, only two studies examined combined treatment versus psychotherapy alone among patients with severe depression, so we cannot be certain whether combined treatment is superior for these people. Individual patient data meta‐analyses have suggested that baseline depression severity does not moderate the efficacy of CBT versus antidepressant treatment, or CBT over pill placebo. This supports the notion that combined treatment should be the first option for moderate and probably also severe depression.…”
Section: Discussionmentioning
confidence: 70%
“…For example, having an anxiety disorder, which was likely associated with coming from the studies in the sample that addressed anxiety disorders, had a much stronger predictive value for non-responder. Similarly, Furukawa et al (2017) found that rate of improvement did not interact with baseline severity in an individual patient data meta-analysis of CBT for depression versus pill-placebo (n=509), and that result does not share the same potential sources of bias. Bower et al (2013) is an individual patient-data meta-analysis.…”
Section: Baseline Severity As a Predictor Of Treatment Outcomementioning
confidence: 96%
“…The treatment significance of severity has been studied in several different ways. There are controlled studies, effectiveness studies, pooled analyses, and meta‐analyses examining the impact of severity on particular treatments, comparing treatments across a range of severity, comparing medication and placebo across a range of severity, comparing psychotherapy and control groups across a range of severity, comparing treatments amongst severely depressed patients, and examining whether severity predicts short‐term outcome, treatment resistance, longer‐term outcome, and relapse.…”
Section: Severity Of Depressionmentioning
confidence: 99%